RESISTANCE TO ANTIPLATELET DRUGS IN PATIENTS WITH ISCHEMIC HEART DISEASE - D. H. Aynetdinova; A. E. Udovichenko; V. A. Sulimov (Рациональная фармакотерапия в кардиологии, 2015)
The clinical, cell and genetic factors are distinguished among reasons for resistance to antiplatelet drugs. There are many methods to detect sensitivity to antiplatelet drugs, but they all have disadvantages. Moreover, there is no unified approach for interpretation of received results, and no recommendations for their practical use. It is necessary to work out unified procedure to assess platelet function, to define indications for its usage and to work out unified criteria of resistance. Individualized approach and each patient’s peculiarities consideration are essential when prescribing antiplatelet therapy.